2021
DOI: 10.1111/jipb.13036
|View full text |Cite
|
Sign up to set email alerts
|

Light participates in the auxin‐dependent regulation of plant growth

Abstract: Light is the energy source for plant photosynthesis and influences plant growth and development. Through multiple photoreceptors, plant interprets light signals through various downstream phytohormones such as auxin. Recently, Chen et al. (2020) uncover a new layer of regulation in IPyA pathway of auxin biosynthesis by light. Here we highlight recent studies about how light controls plant growth through regulating auxin biosynthesis and signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…These pathways work together to enhance SWR1 complex‐mediated H2A.Z deposition at YUC9 to repress its expression, leading to reduced IAA biosynthesis and inhibited hypocotyl elongation (Figure 8B). Previous studies showed that light controls plant growth through regulation of auxin biosynthesis and signaling (Xu et al, 2018; Chen et al, 2020; Mao et al, 2020; Yang et al, 2020b; Lv et al, 2021). This study provides a new insight into the mechanism of phyB‐mediated photomorphogenesis, which involves phyB regulation of H2A.Z deposition at YUC9 .…”
Section: Discussionmentioning
confidence: 99%
“…These pathways work together to enhance SWR1 complex‐mediated H2A.Z deposition at YUC9 to repress its expression, leading to reduced IAA biosynthesis and inhibited hypocotyl elongation (Figure 8B). Previous studies showed that light controls plant growth through regulation of auxin biosynthesis and signaling (Xu et al, 2018; Chen et al, 2020; Mao et al, 2020; Yang et al, 2020b; Lv et al, 2021). This study provides a new insight into the mechanism of phyB‐mediated photomorphogenesis, which involves phyB regulation of H2A.Z deposition at YUC9 .…”
Section: Discussionmentioning
confidence: 99%
“…Early studies on plant responses to shading mainly focused on the verification of SAR-related gene functions [ 28 , 29 ]. Many studies have shown that PIFs are positive regulators of SAR.…”
Section: Mechanism Of Light and Auxin Integration In Sar And Strmentioning
confidence: 99%
“…Previous studies have shown that auxin plays an essential role in plant growth and female gametophyte development (Ceccato et al, 2013;Kneuper et al, 2020;Lv et al, 2020). To determine whether auxin distribution is altered in the grdp2-3 mutant, we crossed the DR5:GFP reporter line and examined the spatial distribution of auxin (Benkova et al, 2003) in the grdp2-3 plants.…”
Section: Auxin Distribution During Gametogenesis Is Disrupted In Grdp2 Ovulementioning
confidence: 99%